منهج الشيخ إبراهيم إنياس في كتابه "رياض التفسير" لنماذج مختارة في سورتي البقرة وآل عمران : دراسة تحليلية /: - ويدراوغو، سعيد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This thesis is an attempt to explain the methodology used by Sheikh Ibrahim Inyas in his book entitled: Riyaì At-Tafsir Lil-Qur'an Al-Karim through two chapters: Baqarah and Al-'Imran. This methodology is the appropriation of two approaches by Sheikh Inyas—interpretation of Qur'an through of traditional and rational interpretation of the Qur'an. Furthermore, while the former entails the interpretation of Qur'an by Qur'an itself; or interpretation of Qur'an by Sunnah (the prophetic tradition): or interpretation of Qur'an by the statements and opinions of the companions of the prophet (peace be upon him) and the followers. The latter, however, means rational and fiqh-oriented interpretation of Qur'an. The research uses inductive method in collecting the related data from primary as well as secondary sources; secondly, it uses analytical method in assessing the data collected, which is a collection of some Quranic verses. Since the theme revolves around Sheikh Ibrahim Inyas, the research provides a short backroad account of his social life as well as the great erudition he left behind. The research has concluded some findings, the most important of which are: Sheikh Inyas uses a combination of two methods in the interpretation the Qur'an— al-Tafsir bi al-Ma'thur (interpretation of by way of traditional scholarship) and al-Tafsir bi ar-Ra'y (rational and fiqh-oriented interpretation of Qur'an). He does not literally quote from Al-Mahalli and As-Suyuti, but rather critically assess their opinions and statements and sometimes even provides his own opinion to correct what he thinks to be an error. He criticizes some Israelite ancient accounts by using Islamic historiography or laws of narration. He focuses on the verses that deal with juristic issues by displaying various statements that belong to different schools of thought. He relies chiefly on linguistic method to interpret Qur'an considering it a key and essential factor and instrument to solid understanding of Qur'an. Finally, the research recommends the following: 1- more and extensive researches on Muslim scholars of Africa: their thought, erudition, and intellectual contribution to the body of knowledge and academia. 2- A comparative study between Riyaì At-Tafsir and other books of exegesis. 3- More extensive study on Sheikh Inyas: his heritage, thought, and development projects.